Theoretical treatment of the resonant hyper-Raman scattering of light in crystals - Semenova, L.E.; Prokhorov, K.A. (Functional Materials, 2004)
The work is aimed at discussion of different mechanisms of the resonant hyper-Raman scattering of light with participation of excitons in semiconductor crystals and analysis of their contributions to the scattering intensity.